2020
DOI: 10.1111/aogs.13893
|View full text |Cite
|
Sign up to set email alerts
|

Presence of amniotic fluid sludge and pregnancy outcomes: A systematic review

Abstract: Introduction: Several studies acknowledge that the presence of amniotic fluid sludge (AFS) is an independent predictive factor for preterm birth. In the present systematic review, we summarize research that focuses on the comparison of pregnancy outcomes among women with and without AFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Statistical heterogenicity was high (I 2 = 44%) and the trial sequential analysis revealed that the required sample size (2837 women) to reach concrete conclusions was not reached (Figs. 10,11).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Statistical heterogenicity was high (I 2 = 44%) and the trial sequential analysis revealed that the required sample size (2837 women) to reach concrete conclusions was not reached (Figs. 10,11).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…An ultrasound-detectable sludge was shown to be a risk for SPTB in this study. A systematic review showed that patients with sludge had higher incidences of SPTB [ 15 , 17 ]. Recent studies also showed that amniotic fluid sludge is an independent risk factor for PTB [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modulating factors may include: (1) the load and composition of maternal microbiota [ 23 ], microbial type (e.g., high virulent Gram-negative bacteria and relatively low virulent Ureaplasma spp.) [ 19 ], pathogenic factors of microorganisms (e.g., toxin, biofilm-forming capacity) [ 36 ], and microbial exposure in a sequential manner [ 2 ]; (2) maternal pro- and anti-inflammatory immune status is dynamically regulated across gestational trimesters to tolerate the semi-allogenic fetus while confronting potential pathogens and preparing to trigger delivery [ 37 ]; (3) the developing fetal immune system is not less able to elicit inflammatory responses upon microbial exposure, as compared to their term counterparts and adults, but may incline to imbalanced hyper-inflammation [ 38 , 39 ].…”
Section: Intra-amniotic Infection: Microbes Maternal-fetal Inflammati...mentioning
confidence: 99%